Practicing safe sects : religious reproduction in scientific and philosophical perspective - Shults, F. LeRon. (Philosophical Studies in Science and Religion, 2018)
Where do gods come from - and what is the cost of bearing them? In Practicing Safe Sects F. LeRon Shults argues for the importance of having "the talk" about the causes and consequences of participating in religious sects. To survive and thrive as a social species, we humans are likely to continue needing some kind of sects (as well as sex) for quite some time. But can we learn how to practice safe sects? Can we live together in healthy and productive social networks without reproducing the superstitious beliefs and segregative behaviors that are engendered and nurtured by shared ritual engagement with imagined supernatural agents? In this provocative and timely book, Shults provides scientific and philosophical resources for answering these questions.